European Multicenter Evaluation of High-Density DNA Probe Arrays for Detection of Hepatitis B Virus Resistance Mutations and Identification of Genotypes - Tran, N. (American Society for Microbiology, 2006)
Polymorphisms along the hepatitis B virus (HBV) genome have an impact on disease outcome, sensitivity to antiviral treatment, escape from vaccination, and laboratory diagnosis. We have designed a diagnostic tool based on duplex amplification of the whole HBV genome and a high-density DNA chip designed to detect 245 mutations, 20 deletions, and 2 insertions at 151 positions and to determine the genotype of the virus in serum. Assay performances were evaluated with 170 samples, characterized by determination of viral load and sequencing of the Pol, S, and precore genes and the basal core promoter. One hundred fifty-three samples (90%) could be amplified and analyzed by the chip. Only two samples with more than 10(3) genome copies/ml could not be analyzed. Genotype had no impact on analytical sensitivity. Reproducibility studies showed no difference between repeats for codon and genotype determination. Genotype determination by sequencing and the chip were concordant in 148 of 151 samples. Twelve thousand one hundred sixty-one codons were analyzed by both techniques. Only 89.4% could be determined by sequencing, and among the remaining 11,335 codons, 92.8% were identical by sequencing and the chip. Failures to identify an amino acid by the chip were mainly due to reduced hybridization efficiency attributed to unexpected polymorphisms. Optimization of the chip-based reagent for the analysis of the HBV genome is ongoing. This first evaluation showed that DNA chip technology can provide important information in relation to the clinical management of chronic hepatitis B.